Oxygen free graphene-doped TiO₂ technique for photo anode dye-sensitised solar cells - AlSultan, Hussein Abdulsalam Ali (2019)
The 3rd generation solar cells that are represented in this work by Dye Sensitised solar cells have attracted much attention in the last few years due to the lower cost, relatively environmentally friendly, and variety of shapes for installation. However, the most common challenges that are present in enhancing those solar power cells are the electron-hole recombination that occurs in the photoanode layer due to the high bandgap of the semiconductor, and a porous structure on the surface of titanium dioxide TiO2. Many research works have addressed this issue by doping the semiconductor with a highly conductive material, to reduce the high bandgap and harness more electron to the external circuit. However, the process of doping graphene is done by oxidising graphite into graphite oxide that contained bulks of graphene, which is also called as hummers’ method. This process, that contaminates the graphene with oxygen, can profoundly reduce the graphene conductivity, even after the reduction process with the modified hummers’ method. Still, there is too much oxygen between graphene sheets. The aim of this study is to enhance the power conversion efficiency of the DSSC by doping contamination-free graphene nanoplatelets GNP into TiO2 matrix. This study has hypothesised that graphene is a hydrophobic phase of carbon that needs oxidisation in order to be orderly and uniformly dispersed into the TiO2 structure. However, with a precision amount of adhesive materials and continues dispersion, graphene in GNP form can be doped into the diluted TiO2 Pure Anatase and synthesising a nanocomposite past. This method will enable the doping of graphene without risking contaminating it with oxygen. Doctor Blade method, which includes placing the thin film on FTO glass has been conducted in this study, with platinum as the counter electrode, and electrolyte as a mediator. The experiment characterisations involve Raman Spectroscopy, FTIR, UVVis, FESEM, EDX, and photocurrent-voltage density. The observation of graphene doped TiO2 using FESEM indicated a formation of TiO2 molecules around graphene sheets, and this formation helps to lower the bandgap and to create pathways for electron mobility using graphene sheets. The weight percentage and atomic level of the nanocomposite show lower oxygen level than that of modified hummers’ method nanocomposite, and with much higher carbon weight percentage and atomic level. There is an indication of low defects on the nanocomposite thin film and between D and G bands, ID/IG = 0.36. Furthermore, the light absorption has increased accordingly with higher ratios of graphene in the thin film, as it reached Eg = 2.64 eV on 1.5 wt% of graphene in the nanocomposite. However, the improved efficiency was calculated using the power conversion efficiency formula, which was at 0.2 wt% of graphene, with a bandgap that decreased to Eg =3.01 eV. In conclusion, the proposed method has successfully enhanced the photoanode by increasing the voltage-current density of the active area.